2019
DOI: 10.3390/ijms20133179
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Computational Analysis Highlights unique miRNA Signatures in the Subventricular Zone and Striatum of GM2 Gangliosidosis Animal Models

Abstract: This work explores for the first time the potential contribution of microRNAs (miRNAs) to the pathophysiology of the GM2 gangliosidosis, a group of Lysosomal Storage Diseases. In spite of the genetic origin of GM2 gangliosidosis, the cascade of events leading from the gene/protein defects to the cell dysfunction and death is not fully elucidated. At present, there is no cure for patients. Taking advantage of the animal models of two forms of GM2 gangliosidosis, Tay-Sachs (TSD) and Sandhoff (SD) diseases, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Other LSDs also present alterations in miRNAs from the miR-17-92 family. This is the case for GM2-Gangliosidosis deficiencies, such as Tay-Sachs and Sandho diseases, in which a panel of nine miRNAs that included miR-19a have been identified as highly downregulated [105].…”
Section: Mirnas Of Mir-17-92 Cluster Involved In Lsd and Npcmentioning
confidence: 98%
“…Other LSDs also present alterations in miRNAs from the miR-17-92 family. This is the case for GM2-Gangliosidosis deficiencies, such as Tay-Sachs and Sandho diseases, in which a panel of nine miRNAs that included miR-19a have been identified as highly downregulated [105].…”
Section: Mirnas Of Mir-17-92 Cluster Involved In Lsd and Npcmentioning
confidence: 98%
“…For example, cholesterol accumulates in late endosomes and lysosomes in the juvenile form of Niemann Pick type C disease characterized by progressive neurodegeneration similar to AD, including NFTs formation and increased APP amyloidogenic processing [ 206 , 303 , 304 ]. An extensive study reported APP-CTFs, Aβ peptide, and α-Synuclein accumulation in the Sandhoff mouse model [ 305 , 306 , 307 ] and ganglioside-bound Aβ-peptide in post-mortem human brains of patients with GM1 gangliosidosis and GM2 gangliosidosis [ 308 ]. Other evidence came from the presence of soluble Aβ(1-40)-peptide in post-mortem brains of patients with Mucopolysaccharidosis type 1 [ 309 ], in the mouse models of Mucopolysaccharidosis type IIIB [ 310 ], and the neuropathic form of Gaucher disease [ 311 ].…”
Section: Cross-talk Between Metabolic Dysfunctions Neuroinflammatmentioning
confidence: 99%